On the difficulty of understanding the sense of movement in Aristotle (Revista Archai, 2017)
<script src="//m.addthis.com/live/red_lojson/300lo.json?si=59caf6e10fdce979&bkl=0&bl=1&pdt=579&sid=59caf6e10fdce979&pub=archaijournal%40unb.br&rev=v8.1.0a-wp&ln=en&pc=men&cb=0&ab=-&dp=periodicos.unb.br&fp=index.php%2Farchai%2Farticle%2Fview%2F18098&fr=index.php%2Farchai%2Fissue%2Fview%2F1706%2FshowToc&of=0&pd=0&irt=0&vcl=0&md=0&ct=1&tct=0&abt=0&cdn=0&pi=1&rb=2&gen=100&chr=utf-8&mk=Ancient%20Philosophy%2CAristotle%2CPhilosophy%20of%20Nature%2COntology%2CMotion&colc=1506473697973&jsl=1&uvs=59caf6e1cdd3ee47000&skipb=1&callback=addthis.cbs.oln9_242855342179825630" type="text/javascript"></script> On the difficulty of understanding the sense of movement in Aristotle | Barbosa | Archai: Journal on the origins of Western thought <!-- Base Jquery --> <!-- Compiled scripts --> <!-- Included only for namespace definition --> Despite the Greek tradition general understanding of the notion of movement, that is, according to its negative aspects and analogous to the non-being, Aristotle elaborates in his Physics the notion of movement so that it can be considered in act, as something determinate and positive concerning the being. Nevertheless, the commentators tradition since Simplicio separates the notion of movement from its original character, turning it into an incomplete and self-annihilating act as well as an intermediary between the being and the non-being, or even, “the passage from potency to act”. Such investigation aims at understanding the notions of movement and change (especially according to the books III and V), avoiding reductions and undue appropriations, in search for an adequate way to interpret such capital notions coherently to the Physics in order to finally restitute it to its appropriate status and position.